2020
DOI: 10.23955/rkl.v15i2.14788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Activator Type on Activated Carbon Characters from Teak Wood and The Bleaching Test for Waste Cooking Oil

Abstract: The starting material for activated carbon was biomass from teak woodcutting, which consists of 47.5% cellulose, 14.4% hemicellulose, and 29.9% lignin. The surface area and iodine number of activated carbons are the factors determining the adsorption ability. This study aims to determine the effect of the activator type on activated carbon characters and test the absorption ability for waste cooking oil. The synthesis stages include carbonization, chemical activation, and then physics activation. The activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…High amount of ash in adsorbents is undesirable since it may interfere in the adsorptive capacity of the adsorbent [13]. Also, higher amounts of moisture content and fixed carbon contents are desired in adsorbents [20]. Since the activated carbon obtained from both sources are low in ash contents and high in moisture and fixed carbon contents, it is therefore expected that they perform well in the CPO bleaching process.…”
Section: Proximate Analysis Of the Activated Carbon Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…High amount of ash in adsorbents is undesirable since it may interfere in the adsorptive capacity of the adsorbent [13]. Also, higher amounts of moisture content and fixed carbon contents are desired in adsorbents [20]. Since the activated carbon obtained from both sources are low in ash contents and high in moisture and fixed carbon contents, it is therefore expected that they perform well in the CPO bleaching process.…”
Section: Proximate Analysis Of the Activated Carbon Samplesmentioning
confidence: 99%
“…The researchers also discovered that Fuller's earth performed better than the rest in color reduction but activated carbon performed best in the removal of xanthophylls (Y-Band) from the CPO sample. Sriatun et al [20] also investigated the ability of activated carbon from teak wood in CPO bleaching and discovered them to be effective but dependent on activator type. Alhassan et al [7] used activated rice husk ash to bleach CPO and found it to be effective in the bleaching process and for chromophore deactivation.…”
Section: Introductionmentioning
confidence: 99%